ANALISIS RENDAHNYA KEAKTIFAN PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS 3 SEKOLAH DASAR - Kartika Sari, Dewi; Nanda Faradita, Meirza; Adi Putra, Deni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low level of student activeness in IPAS learning in class III-C at SD Muhammadiyah 9 Surabaya. Most students still showed a lack of participation during the learning process. This study aims to describe the low student activeness in the IPAS learning process in grade III of elementary school. The research employed a qualitative method with a descriptive approach. Data were collected through observations, interviews, and questionnaires. The collected data were then analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that student activeness in IPAS learning remains low, as most students tend to be passive even though some have shown positive responses, thus requiring approaches that better encourage active participation.